2014
DOI: 10.1057/crr.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perception of CSR: Modeling Psychological Motivators

Abstract: Scholars have called for more specific model development and a better defined process to predict the outcomes of Corporate Social Responsibility (CSR) activity. This paper builds on previous work in the field of CSR from a consumer perspective. Psychological dimensions related to consumer perception of CSR were explored through consumer survey data (N = 343) using exploratory factor analysis and structural model verification through confirmatory factor analysis. Three distinct latent variables entitled Public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Starting with gender, findings were fairly consistent, in that the socially responsible consumer tended to be female (e.g., Berkowitz and Lutterman, 1968 ; Webster, 1975 ; Gupta and Singh, 2017 ). Most CSR studies confirmed these results by showing that women were more likely to perceive CSR actions as positive (e.g., Patino et al, 2014 ; Kim and Kim, 2016 ), while only a few studies detected no gender effect on perceived CSR (e.g., Mueller, 2014 ).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Starting with gender, findings were fairly consistent, in that the socially responsible consumer tended to be female (e.g., Berkowitz and Lutterman, 1968 ; Webster, 1975 ; Gupta and Singh, 2017 ). Most CSR studies confirmed these results by showing that women were more likely to perceive CSR actions as positive (e.g., Patino et al, 2014 ; Kim and Kim, 2016 ), while only a few studies detected no gender effect on perceived CSR (e.g., Mueller, 2014 ).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 95%
“…For the perception of CSR activities, the findings are not consistent. While some scholars suggest that middle-aged consumers react positively to CSR activities (e.g., Carrigan et al, 2004 ; Tian et al, 2011 ), others detected no age differences (Mueller, 2014 ) or consistent effects (Pérez and Rodríguez del Bosque, 2013a ).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Citing a study by Brammer and Paveline, in their paper [22] discuss that Corporations enhance their legitimacy and reputation through disclosure of information regarding CSR activities. A study by [23] concluded that cause-related donations by corporations are altruistic and basically self-serving to the corporation. In yet another study by [24] it was found that consumers assume that CSR activities are motivated by image promotional goals of a firm.…”
Section: Perceived Csrmentioning
confidence: 99%
“…La segunda etapa fue exploratoria y en ella se determinó la sustentabilidad de la estructura factorial de cuatro responsabilidades sociales básicas, propuesta por el modelo teórico de Carroll. Para ello se realizó un análisis de validez de constructo (análisis factorial exploratorio), utilizando el método de componentes principales y rotación varimax, esto a partir del supuesto de que los factores que conforman el instrumento son independientes (Cea, 2002) y en correspondencia con estudios previos (Aupperle et al, 1985;Maignan, 2001;Mueller, 2014). Una vez determinada la estructura factorial del instrumento, se procedió al cálculo de la fiabilidad de la escala, en general y por cada uno de los factores resultantes.…”
Section: Instrumento De Mediciónunclassified